Quantum Dots - Theory and Applications 2015
DOI: 10.5772/60823
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Dots Prepared by Droplet Epitaxial Method

Abstract: In this work, we are dealing with the droplet epitaxially prepared quantum dots. This technology is not only an alternative way of the strain induced technique to prepare quantum dots, but it allows us to make various shaped nano structures from various material. The present paper deals not only with the so called conventional shaped quantum dot but also with the ring shaped dot, with the inverted dot and with dot molecules as well. Their thechnology, opto-electronical and the structural properties are also di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…The growth mechanism of InGaN microplates has been extensively studied [ 16 , 18 , 24 , 30 , 31 , 32 , 33 , 34 , 35 ], while the CL properties of full-composition-graded In x Ga 1−x N film are rarely reported, especially InGaN microplates. We found that the CL luminescence intensity of microplates inside was significantly weaker than microplates outside.…”
Section: Resultsmentioning
confidence: 99%
“…The growth mechanism of InGaN microplates has been extensively studied [ 16 , 18 , 24 , 30 , 31 , 32 , 33 , 34 , 35 ], while the CL properties of full-composition-graded In x Ga 1−x N film are rarely reported, especially InGaN microplates. We found that the CL luminescence intensity of microplates inside was significantly weaker than microplates outside.…”
Section: Resultsmentioning
confidence: 99%
“…A few proposed solutions can mitigate the carrier leakage problem in the SK QDs, including dot-in-a-well approach [ 16 ], graded-index separate-confinement-heterostructure [ 17 ], stacking many QD layers [ 18 ], applying the tunnel-injection scheme [ 19 ], or fabricating QDs without the WL. For the latter, one can use the droplet epitaxy (DE) technique in which a group-III element droplet is deposited directly on a substrate undergoing subsequent re-crystallization under deposition of a group-V ad-atoms, spontaneously forming a nanometer-sized island [ 20 ]. First applied to the formation of GaAs QDs on ZnSe substrate [ 21 ], later successfully employed to other semiconductor systems, including the InAs/InP one [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been paid to the crystallization processes which allow modifying the final shape of droplets thus forming various types of nanostructures and complexes [26,[28][29][30][31][32][33][34]. Nucleation and growth of islands during deposition of group III atoms, which has no less significance, is poorly investigated because droplet epitaxy at a first stage is considered to be realized according to the wellstudied Volmer-Weber growth mechanism [26,[35][36][37]. However, there is a number of questions and contradictions which are observed by different experimental studies.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it should be concluded that the nucleation mechanism during In/GaAs(001) droplet epitaxy still remains unclear. Droplets are naturally considered to be generated by the Volmer-Weber growth mode because the binding energy among metallic adatoms is greater than to the substrate surface [26,37]. However, it runs counter to the observation of critical thickness dependent on the substrate temperature [39].…”
Section: Introductionmentioning
confidence: 99%